Baltic military cooperative projects: case study on effective military assistance programmes - Ito, P K (Cranfield University, 2015)
From 1994, the Baltic states (Estonia, Latvia and Lithuania) undertook a number of cooperative regional military projects with the support of numerous Western countries. In particular, the Baltic Peacekeeping Battalion (BALTBAT) was an example of efficient Western defence cooperation to generate outcomes in order to achieve military and political goals. BALTBAT became the template for other Baltic programmes: the Baltic Naval Squadron (BALTRON), the Baltic Air Surveillance Network (BALTNET) and the Baltic Defence College (BALTDEFCOL). This thesis analysed the Baltic programmes, particularly BALTBAT, as a case study for identifying the elements of a model for effective military assistance projects. The focus was on the broad political decisions agreed upon by the donor and recipient states, such as the selection of development of peacekeeping capabilities, as the basis for military assistance, which provided the foundation for these initiatives. The value of the Baltic programmes as a case study and basis for identifying the elements of a model was enhanced by the fact that they succeeded at a delicate time in a sensitive region. The Baltic states had virtually no military forces upon regaining independence. Russia objected to Baltic state membership in NATO and was sensitive about a build-up of military capabilities close to Russian borders. In spite of these obstacles, the Baltic projects achieved outcomes which supported the military and political goals of the donor and recipient states. Analysis of the Baltic projects highlighted the importance of broad political decisions between donor and recipient states for military assistance initiatives. It also indicated the major factors (subsequently called Mechanisms) resulting from those decisions which were important to the outcomes from these programmes. These Mechanisms comprise the elements of a model which could be of value to academics and practitioners working in the area of military assistance.
Keywords: Baltic States; Military cooperation; Joint military planning; Military administration